3,3′-Bicarbazole-Based Host Molecules for Solution-Processed Phosphorescent OLEDs - Jungwoon Kim; Suhan Lee; Jaemin Lee; Eunhee Lim; Byung Jun Jung (Molecules, 2018)
Solution-processed organic light-emitting diodes (OLEDs) are attractive due to their low-cost, large area displays, and lighting features. Small molecules as well as polymers can be used as host materials within the solution-processed emitting layer. Herein, we report two 3,3′-bicarbazole-based host small molecules, which possess a structural isomer relationship. 9,9′-Di-4-n-butylphenyl-9H,9′H-3,3′-bicarbazole (BCz-nBuPh) and 9,9′-di-4-t-butylphenyl-9H,9′H-3,3′-bicarbazole (BCz-tBuPh) exhibited similar optical properties within solutions but different photoluminescence within films. A solution-processed green phosphorescent OLED with the BCz-tBuPh host exhibited a high maximum current efficiency and power efficiency of 43.1 cd/A and 40.0 lm/W, respectively, compared to the device with the BCz-nBuPh host.